Membagikan Cahaya Pengetahuan : Pengabdian Kepada Masyarakat Melalui Program Kampus Mengajar - Nurkholis Syukron; My Ismail; Frederikus Antonius Mana; Hafsemi Rapsanjani; Denvy Meidian Daoed (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article discusses the ‘Kampus Mengajar’ programme as an initiative to expand the accessibility of education and knowledge to the community. The main focus of the programme is to contribute positively to the community through the distribution of basic literacy knowledge from Musamus University students to targeted schools. This article will explore the concept, implementation and impact of the ‘Kampus Mengajar’ programme as a form of community service. The ‘Kampus Mengajar’ programme is an initiative of the Indonesian government that involves students as agents of change to assist the learning process in school. The article method used is descriptive with a qualitative approach in several primary schools in Merauke Regency. The results showed that the ‘Kampus Mengajar’ programme successfully improved students‘ learning motivation, teaching skills and introduced creative learning methods that are adaptive to local conditions. In addition, the programme also strengthened the relationship between universities and local communities and improved students' social awareness and professional skills. However, the study also identified some challenges such as programme sustainability and limited resources. Overall, the ‘Kampus Mengajar’ programme has a great potential in improving the quality of education in remote areas and can serve as a model for other community service programmes